Resistance status of mungbean (Vigna radiata (L.) Wilczek) advanced breeding materials against mungbean yellow mosaic India virus. (14th December 2021) - Akram, Mohd; Kamaal, Naimuddin; Pratap, Aditya; Singh, Narendra Pratap
Abstract: Seventy-one advanced breeding lines of mungbean were screened under epiphytotic conditions in the field for resistance against yellow mosaic disease (YMD) using infector technique during Kharif of 2016–2019 at Main Research Farm of IIPR, Kanpur. The identity of the YMD causing virus species was confirmed by PCR using specific primers and found to be as Mungbean yellow mosaic India virus . The average disease rating score recorded for test genotypes ranged from 1–4 as against 7.75 (1–9 disease rating scale) of susceptible check (DGGV-2). Of the 71 test genotypes, 48 showed a good level of resistance (1–2 scale) and of them, genotypes- IPM1205-2, IPM14-49-5, IPM14-10, IPM411-9, IPM709-5-2, IPM14-12-3, IPM14-2, IPM526-11 and IPM 08-11 consistently showed a high level of resistance against YMD for 3 or 4 years with a disease rating score of 1. These genotypes can be exploited as donors for YMD resistance.